A sourcebook for engaging with civil society organizations in Asian Development Bank operations - Asian Development Bank (Manila, Philippines Asian Development Bank, 2021)
Provides guidance on how civil society organizations can be more effectively engaged in Asian Development Bank operations to maximize the benefits for its developing member countries.
Context, Definitions, and Overview - - Policy and Operations - - Consultations with Civil Society Organizations - - Due Diligence, Procurement, and Partnerships - - Due Diligence, Procurement, and Partnerships - - Responsibilities for Civil Society Organization Engagement Within - - Appendixes - - Glossary.
Keywords: Civil society -- Asian Development Bank; Asian Development -- Management